The SCD‐Well randomized controlled trial: Effects of a mindfulness‐based intervention versus health education on mental health in patients with subjective cognitive decline (SCD). Issue 1 (28th November 2018) - Marchant, Natalie L.; Barnhofer, Thorsten; Klimecki, Olga M.; Poisnel, Géraldine; Lutz, Antoine; Arenaza‐Urquijo, Eider; Collette, Fabienne; Wirth, Miranka; Schild, Ann‐Katrin; Coll‐Padrós, Nina; Reyrolle, Leslie; Horney, Deborah; et al.
Abstract: Introduction: Subjectively experienced cognitive decline in older adults is an indicator of increased risk for dementia and is also associated with increased levels of anxiety symptoms. As anxiety is itself emerging as a risk factor for cognitive decline and dementia, the primary question of the present study is whether an 8‐week mindfulness‐based intervention can significantly reduce anxiety symptoms in patients with subjective cognitive decline (SCD). The secondary questions pertain to whether such changes extend to other domains of psychological, social, and biological functioning (including cognition, self‐regulation, lifestyle, well‐being and quality of life, sleep, and selected blood‐based biomarkers) associated with mental health, older age, and risk for dementia. Methods: SCD‐Well is a multicenter, observer‐blinded, randomized, controlled, superiority trial, which is part of the Horizon 2020 European Union‐funded "Medit‐Ageing" project. SCD‐Well compares an 8‐week mindfulness‐ and compassion‐based intervention specifically adapted for older adults with SCD with a validated 8‐week health education program. Participants were recruited from memory clinics in four European sites (Cologne, Germany; London, United Kingdom; Barcelona, Spain; and Lyon, France) and randomized with a 1:1 allocation, stratified by site. Results: The primary outcome, change in anxiety symptoms, and secondary outcomes reflecting psychological, cognitive, social, and biological functioning are assessed at baseline, postintervention, and 4 months after the end of the intervention. Discussion: The study will provide evidence on whether a mindfulness‐based intervention can effect changes in anxiety and other risk factors for cognitive decline and dementia in older adults with SCD and will inform the establishment of intervention strategies targeted at improving mental health in older adults. Highlights: Mindfulness may benefit older adults with subjective cognitive decline (SCD) . SCD‐Well compares an 8‐week mindfulness intervention to a health education course. Patients with SCD were recruited from memory clinics in four countries. Outcomes include anxiety symptoms, psychosocial, cognitive, and biological function. Results will inform future prevention studies and strategies in SCD.